Use of Spondias Mombin fruit pulp as a substrate for biosurfactant production. Issue 1 (1st January 2021) - Ejike Ogbonna, Kenneth; Victor Agu, Chidozie; Okonkwo, Christopher Chukwudi; Tochukwu Ughamba, Kingsley; Akor, Joseph; Njoku, Obioma U.
ABSTRACT: In this study, we explored the possibility of utilizing the succulent pulp of Spondias mombin (SM) as feedstock for the synthesis of biosurfactants by Pseudomonas spp. The cultures were composed of basic mineral medium amended with SM, SM + glucose, glucose (GLC), and nutrient broth (NB) as carbon sources. Biosurfactant production was determined by surface-active properties such as hemolysis, emulsification index (E24 ), drop collapse, oil-spreading assays, and reduction of surface tension. The stability of the biosurfactants was monitored across different temperature and pH regimes while chemical components of the extracted biosurfactants were determined by thin-layer chromatography. Biosurfactants synthesized from SM as sole substrate showed the highest emulsification index (56.35%), oil-spreading capacity (4.4 ± 1.31 cm), hemolysis (3.10 ± 0.02 cm), the shortest time for drop collapse (30 s), and surface tension reduction (24 mN/m). Biosurfactant concentrations ranged from 0.07 ± 0.01 in the NB to 2.08 ± 0.01 g/L in the media amended with SM. Chemical characterization revealed significant concentrations of carbohydrates and lipids in the biosurfactant produced from SM (1.2 ± 0.17 and 0.88 ± 0.04 g/L, respectively) when compared to SM + glucose (0.92 ± 0.05, and 0.62 ± 0.02 g/L, respectively), glucose (0.35 ± 0.04 and 0.13 ± 0.02 g/L, respectively), and nutrient broth (0.06 ± 0.03 and 0.01 ± 0.01 g/L, respectively). The biosurfactants were stable over a wide range of temperature while E24 increased with pH. Our results show the viability of SM fruit pulp as low-cost feedstock for industrial-scale production of biosurfactants using Pseudomonas spp.